Ethnomathematics Exploration of Multiplying and Measuring Activities on The Dome of The Great Mosque of Baitul Hakim Madiun City - Ainun Fisabilillah; Ika Krisdiana; Indra Puji Astuti (Jurnal Pendidikan Matematika (JPM), 2024)
Ethnomathematics is a study that explains the relationship between culture and mathematics. Ethnomathematics is applied as a means to motivate, stimulate, overcome saturation, and give a new feel to mathematical learning. One of the cultures that can be studied with ethnomathematics is the mosque. This study aims to learn mathematical concepts and explore ethnomathematics in the building of the Grand Mosque of Baitul Hakim Kota Madiun, the explored building, namely the dome of the mosque. This qualitative research uses an ethnographic approach with data retrieval using observation, interview, and documentation techniques. The research was conducted at the Grand Mosque of Baitul Hakim City of Madiun with 3 subjects being mosque administrators (secretariat admin, takmir, and marbot). The results of the research were obtained from mathematical concepts and ethnomathematics activities at the Grand Mosque of Baitul Hakim. The mathematical concept obtained is the geometric concept related to the flat construction of isosceles triangles, isosceles trapezoids, ellipses, and limas space structures. The ethnomathematics activity obtained is the activity of measuring and enumerating. Therefore, it can be concluded that there is ethnomathematic activity and there are mathematical concepts in the Grand Mosque of Baitul Hakim Kota Madiun that can be used as a learning resource by educators.